Pengaruh Kesadaran Merek, Citra Merek dan Kepercayaan Merek terhadap Intensi Pembelian Kopi Fore melalui Aplikasi Digital di Jakarta - Arden Saputra; Richard Andrew (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the influence of brand awareness, brand image, and brand trust on the purchase intention of Fore Coffee through digital applications in Jakarta. This research employs a quantitative method by distributing online questionnaires via Google Forms. The sampling technique used is non-probability sampling with a convenience sampling approach. A total of 100 respondents who have purchased Fore Coffee through the Fore Coffee application in the Jakarta area were selected as the sample. Data analysis was conducted using SmartPLS software with the Structural Equation Modeling (SEM) technique. The results indicate that brand awareness, brand image, and brand trust have a positive and significant influence on the purchase intention of Fore Coffee through digital applications in Jakarta.